β-Carotene from Yeasts Enhances Laccase Production of Pleurotus eryngii var. ferulae in Co-culture - Guo, Chaolin; Zhao, Liting; Wang, Feng; Lu, Jian; Ding, Zhongyang; Shi, Guiyang (Frontiers in Microbiology, 2017)
Laccase is widely used in several industrial applications and co-culture is a common method for enhancing laccase production in submerged fermentation. In this study, the co-culture of four yeasts with Pleurotus eryngii var. ferulae was found to enhance laccase production. An analysis of sterilization temperatures and extraction conditions revealed that the stimulatory compound in yeasts was temperature-sensitive, and that it was fat-soluble. An LC-MS analysis revealed that the possible stimulatory compound for laccase production in the four yeast extracts was β-carotene. Moreover, the addition of 4 mg β-carotene to 150 mL of P. eryngii var. ferulae culture broth improved laccase production by 2.2-fold compared with the control (i.e., a monoculture), and was similar to laccase production in co-culture. In addition, the enhanced laccase production was accompanied by an increase of lac gene transcription, which was 6.2-time higher than the control on the fifth day. Therefore, it was concluded that β-carotene from the co-cultured yeasts enhanced laccase production in P. eryngii var. ferulae, and strains that produce β-carotene could be selected to enhance fungal laccase production in a co-culture. Alternatively, β-carotene or crude extracts of β-carotene could be used to induce high laccase production in large scale.